Peran Pelajar Islam Indonesia Dalam Membentuk Karakter Religius Remaja di Kota Bitung - Nurhayati Nurhayati; Sahari Sahari; Wahyudin S. Manaf (Jurnal Ilmiah Iqra', 2022)
The Role of Indonesian Islamic Students in Forming the Religious Character of Youth in Bitung City. This study aims to find out the role of Indonesian Islamic students in shaping the religious character of students in Bitung City and find out what are the obstacles and challenges of Indonesian Islamic Students in shaping the religious character of adolescents in Bitung City.Data collection techniques in this study are observation techniques, interviews and documentation. The research collects data by observing the object of research directly and conducting it to related parties being studied. The data analysis techniques used in the research are data reduction, data presentation, data verification and drawing conclusions. Next, checking the validity of the data was carried out in two ways, namely, source triangulation and technical triangulation.The research findings show that: (1) The role of Indonesian Islamic Students in shaping the religious character of adolescents in Bitung City, namely: a) Indonesian Islamic Student Training, b) ta'lim, c) hospitality, d) Caring Indonesian Muslim Students, e) Advocacy, f) Students, g) visits to several schools. (2) Obstacles and challenges of Indonesian Islamic Students in forming the religious character of youth in Bitung City, namely: a) Adjustment of time, b) Lack of active cadres, c) Lack of communication, and d) lack of cadre loyalty